Application of PD-L1, PD-L2, CD30, CD23 and BCL-6 in Diagnosis and Prognostic Evaluation of Primary Mediastinal Large B-cell Lymphoma - YUAN Ting (Magazine House of Cancer Research on Prevention and Treatment, 2021)
Objective To explore the application value of treatment-related markers PD-L1, PD-L2, CD30, CD23, BCL-2, BCL-6, MUM1 and GATA3 in the diagnosis and prognostic evaluation of primary mediastinal B-cell lymphoma(PMBL). Methods A retrospective study was conducted on 34 patients diagnosed with PMBL, and 31 patients with DLBCL-NOS which was not primary in the mediastinum were taken as control group. The expressions of 8 proteins were detected by IHC staining. Results The median percentages of tumor cells with PD-L1, PD-L2 and CD30 expression in PMBL group were 70% (30%, 90%), 25% (0, 70%) and 17.5% (0, 60%) respectively, which were significantly higher than those in the DLBCL-NOS group (P < 0.05). The positive rates of CD30 and CD23 in PMBL group were 61.76% (21/34) and 76.47% (26/34) respectively, significantly different with those in the DLBCL-NOS group (P=0.000). The survival curve of PMBL patients with CD30 or BCL-6 expression showed a trend of poor prognosis, despite the P value was > 0.05. Conclusion The high expression levels of PD-L1, PD-L2 and CD30 in PMBL are helpful to accurately identify more patients who may respond to immune or targeted therapy. Immunohistochemical staining of PD-L1, PD-L2, CD30 and CD23 is helpful for the differential diagnosis of PMBL and DLBCL-NOS. As candidate prognostic indicators of PMBL, CD30 and BCL-6 should be further studied in a larger number of samples.